PENGARUH PENGGUNAAN EMBACANG TERHADAP KUALITAS DODOL - Sari, Mimi Komala; Yusuf, Liswarty; Holinesti, Rahmi (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2015)
This research was aimed to analyze the effect of using 650 grams, 750 grams, 850 grams and 1000 grams of embacang toward the dodol quality generated in term of the brown color, embacang smell, distinctive flavor embacang, sweetness, chewy and smooth texture of dodol that is generated. This research was an experiment using a completely randomized design, it used embacang with different numbers of 650 grams, 750 grams, 850 grams and 1000 grams with 3 times repetition or experiment that was conducted in culinary workshops of KK FT UNP in November 2014. Panels is a student majoring in Home Economic Department wich consist of 30 people. The independent variable was the use of 650 grams, 750 grams, 850 grams and 1000 grams embacang. The dependent variable is the quality of dodol’s color (Y1), embacang smell (Y2), distinctive flavor embacang (Y3) sweetness (Y4), chewy (Y5) and smooth texture (Y6). The instrument used was a questionnaire that organoleptic through level test using a scale of 1-5 and to test hypotheses using statistical ANAVA with the manual method. If there is significant effect then it will be followed by Duncan test. The test results of organoleptic showed that there was significant effect of using embacang toward the quality smell of dodol, its smell, distinctive flavor embacang and chewy texture. That is generally found in the treatment X4 (1000 grams). So, it stated that there was a difference between the sample X0, X1, X2, X3, X4, but had no effect on the quality of color, sweet taste and smooth texture of dodol, so otherwise there was no significant difference between samples X0, X1, X2, X3, X4.Keywords: embacang, dodol, quality